The Role of Practical Reason in an Empirically Informed Moral Theory - Besser-Jones, Lorraine (Ethical theory and moral practice, 2012)
Empirical research paints a dismal portrayal of the role of reason in morality. It suggests that reason plays no substantive role in how we make moral judgments or are motivated to act on them. This paper explores how it is that an empirically oriented philosopher, committed to methodological naturalism, ought to respond to the skeptical challenge presented by this research. While many think taking this challenge seriously requires revising, sometimes dramatically, how we think about moral agency, this paper will defend the opposite reaction. Contrary to what recent discussions lead us to expect, practical reason is not simply a philosophical fiction lacking empirical roots. Empirical research does not exclude the possibility that practical reason can play a substantive role; rather, there is evidence that it can help us both to determine our first personal moral judgments and to motivate us to act on them.